Respuesta :
we know that
The y-intercept is the value of the function when the value of x is equal to zero
Step [tex]1[/tex]
Find the y-intercept of f(x)
[tex]f(x)=4x-1[/tex]
for [tex]x=0[/tex]
[tex]f(0)=4*0-1[/tex]
[tex]f(0)=-1[/tex]
the y-intercept of f(x) is equal to [tex]-1[/tex]
Step [tex]2[/tex]
Find the equation of the line g(x)
Let
[tex]A(1,3)\\B(4,6)\\C(7,9)[/tex]
Find the slope AB
the slope m is equal to
[tex]m=\frac{(y2-y1)}{(x2-x1)}[/tex]
substitute the values
[tex]m=\frac{(6-3)}{(4-1)}[/tex]
[tex]m=1[/tex]
with the slope and the point A find the equation of the line
[tex]y-y1=m(x-x1)[/tex]
[tex]y-3=1*(x-1)[/tex]
[tex]y=x-1+3[/tex]
[tex]y=x+2[/tex]
therefore
the function g(x) is equal to
[tex]g(x)=x+2[/tex]
Step [tex]3[/tex]
Find the y-intercept of g(x)
[tex]g(x)=x+2[/tex]
for [tex]x=0[/tex]
[tex]g(0)=0+2[/tex]
[tex]g(0)=2[/tex]
the y-intercept of g(x) is equal to [tex]2[/tex]
therefore
the answer is the option
B The function g(x) has a higher y-intercept.
Answer:
B
Step-by-step explanation:
I just took the test and its correct!